Effects of Child Abuse on Academic Performance of Primary School Pupils in Kwande Local Government Area of Benue State, Nigeria - Tersoo Timothy Tsegba; Ibrahim Ologele; Kafayah Adeola Jidda; Joseph Abiodun Stephen (IJORER : International Journal of Recent Educational Research, 2021)
Several factors contributing to the low standard of education in Nigeria where child abuse identified to be an important factor. The study, therefore, investigates the effect of child abuse on the academic performance of primary school pupils in the Kwande Local Government Area of Benue State, Nigeria. The population of the study comprised all primary school pupils and their teachers in the study area. The descriptive research design of survey type employed for the study. A multi-stage sampling technique was used to select ten public primary schools out of fifty seven public primary schools in the study area. Nine hundred and forty–six (946) respondents selected for the study. Researchers developed a questionnaire validated by three experts from the related field was used as an instrument for the study. The findings revealed that child abuse has a significant effect on pupils participation in the class and also had a significant effect on pupils assessment in the Kwande Local Government Area of Benue State, Nigeria. The researchers' recommends among others that the government should carry out an enlightenment campaign through mass media for parents and guardians on the consequences of child abuse on the educational achievement of primary school pupils to improve their participation in classes as well as improve their assessment grades in test and examination.